Cholecystocolonic fistula secondary to ascending colon diverticular disease: A case report - Fatima Bhojani; Wasim Ahmed Memon; Muhammad Nadeem Ahmad; Mallick Muhammad Zohaib Uddin; Sibgha Khan; Naila Nadeem; Faheemullah Khan; Uffan Zafar (Clinical Case Reports, 2024)
Key Clinical Message Cholecystocolonic fistula occurring as a complication of colonic diverticular disease is a rarely encountered clinical entity in which the patient may remain asymptomatic or present with vague abdominal or systemic symptoms. Imaging studies are usually not very reliable or effective in detecting direct communication between gallbladder and colon. However, indirect signs such as pneumobilia, gallstones, gallbladder adherent to colon and colonic diverticulosis may help reach the diagnosis. Treatment of cholecystocolonic fistula in symptomatic patients is usually surgical. However, in asymptomatic patients or patients with risk factors and comorbidities, non‐surgical options such as conservative management or biliary stenting can be considered.